Perspectives on global mycotoxin issues and management from the mycokey maize working group - Logrieco, A.F.; Battilani, P.; Leggieri, C.; Haesaert, G.; Jiang, Y.; Lanubile, A.; Mahuku, George S.; Mesterhazy, A.; Ortega Beltran, A.; Pasti, M.A.; Smeu, I.; Torres, A.; et al. (Scientific Societies, 2021)
During the last decade, there have been many advances in research and technology that have greatly contributed to expanded capabilities and knowledge in detection and measurement, characterization, biosynthesis, and management of mycotoxins in maize. MycoKey, an EU‐funded Horizon 2020 project, was established to advance knowledge and technology transfer around the globe to address mycotoxins impacts in key food and feed chains. MycoKey included several working groups comprised of international experts in different fields of mycotoxicology. The MycoKey Maize Working Group recently convened to gather information and strategize for the development and implementation of solutions to the maize mycotoxin problem in light of current and emerging technologies. This feature summarizes the Maize WG discussion and recommendations for addressing mycotoxin problems in maize. Discussions focused on aflatoxins, deoxynivalenol, fumonisins, and zearalenone, which are the most widespread and persistently important mycotoxins in maize. Although regional differences were recognized, there was consensus about many of the priorities for research and effective management strategies. For pre-harvest management, genetic resistance and selecting adapted maize genotypes, along with insect management, were among the most fruitful strategies identified across the mycotoxin groups. For post-harvest management, the most important practices included timely harvest, rapid grain drying, grain cleaning, and carefully managed storage conditions. Remediation practices such as optical sorting, density separation, milling, and chemical detoxification were also suggested. Future research and communication priorities included advanced breeding technologies, development of risk assessment tools, and the development and dissemination of regionally relevant management guidelines.